2023
DOI: 10.1002/advs.202302953
|View full text |Cite
|
Sign up to set email alerts
|

Targeting USP8 Inhibits O‐GlcNAcylation of SLC7A11 to Promote Ferroptosis of Hepatocellular Carcinoma via Stabilization of OGT

Jianing Tang,
Guo Long,
Kuan Hu
et al.

Abstract: Hepatocellular carcinoma (HCC) is a lethal and aggressive human malignancy. The present study examins the anti‐tumor effects of deubiquitylating enzymes (DUB) inhibitors in HCC. It is found that the inhibitor of ubiquitin specific peptidase 8 (USP8) and DUB‐IN‐3 shows the most effective anti‐cancer responses. Targeting USP8 inhibits the proliferation of HCC and induces cell ferroptosis. In vivo xenograft and metastasis experiments indicate that inhibition of USP8 suppresses tumor growth and lung metastasis. DU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Total GSH was detected using the Glutathione Assay Kit (Beyotime Biotechnology) according to the instructions of manufacturer as we previously described 77 . The experiment was repeated three times with three replicates per sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total GSH was detected using the Glutathione Assay Kit (Beyotime Biotechnology) according to the instructions of manufacturer as we previously described 77 . The experiment was repeated three times with three replicates per sample.…”
Section: Methodsmentioning
confidence: 99%
“…Iron assay kit (Sigma; Cat. MAK025) was used for the measurement intracellular ferrous (Fe2+) iron according to the instructions of manufacturer as we previously described 77 . The experiment was repeated three times with three replicates per sample.…”
Section: Methodsmentioning
confidence: 99%
“…OGT has been reported to be regulated by the balance of ubiquitination and deubiquitination 9,10,12,13 . The E3 ligases XIAP and E6AP could promote the ubiquitin-dependent proteasome degradation of OGT 10,11 .…”
Section: Loss Of Fbxo31 Increases O-glcnacylation and Promotes Endome...mentioning
confidence: 99%
“…Cancer cells often hijack embryonic programs to support their uncontrolled proliferation and cell fate transition, adopting a metabolic lifestyle relying on aerobic glycolysis (Warburg effect). Elevated O-GlcNAcylation has been observed in many cancer cell lines [5][6][7][8] , probably as a result of its increased nutrient consumption, or imbalanced enzymatic activity of OGT and OGA due to somatic mutations or altered protein stability [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that ME1 is a potential therapeutic target for the treatment of liver ischemia-reperfusion injury or other diseases associated with ferroptosis. Using drug screening, Tang et al ( 104 ) found that USP8 small molecule inhibitors can significantly inhibit the activity of liver cancer cells. Mechanism studies have shown that USP8 modified OGT protein through deubiquitination to improve the stability of the protein, which subsequently regulated SLC7A11 through glycosylation and inhibited ferroptosis in hepatocellular carcinoma, thus promoting the occurrence of liver cancer.…”
Section: Ferroptosis In the Combination Therapy Of Cancermentioning
confidence: 99%